2012
DOI: 10.1590/s0101-31222012000100017
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de soja colhidas em duas épocas após dessecação com glyphosate

Abstract: RESUMO -A dessecação de plantas de soja em pré-colheita com glyphosate vem se tornando prática rotineira entre os produtores, apesar de não ser recomendada, pois pode comprometer a qualidade fisiológica das sementes. Objetivou-se avaliar os efeitos da dessecação das plantas em pré-colheita com glyphosate na qualidade fisiológica de sementes de soja colhidas em duas épocas após a aplicação. O delineamento experimental foi em blocos ao acaso, com quatro repetições, em esquema de parcelas subdivididas. As parcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
4
9
0
7
Order By: Relevance
“…They found that only seeds produced from plants desiccated with glyphosate at R6.5 showed a reduction in seedling length. A similar result was also observed by Toledo et al (2012) who found glyphosate effect on root length, hypocotyl length and total height of the seedlings. Lamego et al (2013) obtained a higher rate of soybean seedling emergence when seeds were derived from plants desiccated in R6.0.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…They found that only seeds produced from plants desiccated with glyphosate at R6.5 showed a reduction in seedling length. A similar result was also observed by Toledo et al (2012) who found glyphosate effect on root length, hypocotyl length and total height of the seedlings. Lamego et al (2013) obtained a higher rate of soybean seedling emergence when seeds were derived from plants desiccated in R6.0.…”
Section: Discussionsupporting
confidence: 89%
“…During the seed maturation period, when the rapid translocation of reserves is still occurring and the photosynthesis rate is lowest, premature death of the plant prevents the complete degradation of chlorophyll, which results in the production of greenish and low quality seed (Marcos Filho, 2005). Toledo et al (2012) verified that delay in harvesting reduces the germination of seeds produced by soybean plants desiccated with glyphosate in pre-harvest. According to Carvalho and Nakagawa (2012) seeds have maximum strength at the physiological maturity point (stage R7.0) and from that stage onwards the value decreases as a function of the environmental and microbiological conditions to which the seeds are submitted.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The lack of significance found in the results may be because desiccant applications were held by the time bean seeds were at physiological maturity, when they reach a maximum dry matter accumulation (TOLEDO et al, 2012). These results are supported by observations made by KAPPES et al (2012), who found no differences for yield components of common bean grown in winter and desiccated with paraquat at physiological maturity.…”
Section: Resultssupporting
confidence: 73%
“…Nevertheless, some key factors must be considered including herbicide type and application rate to avoid drops in production and seed quality (TOLEDO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%